Oxidized-LDL and Fe3+/ascorbic acid-induced oxidative modifications and phosphatidylserine exposure in human platelets are reduced by melatonin - (:unkn) unknown (My University, 2009)
Low-density lipoprotein (LDL) modifications and platelet activation are major risk factors for cardiovascular diseases. When platelets are exposed to oxidative stress, they become activated. Oxidized LDL (ox-LDL) and metal-catalysed oxidation systems such as Fe3+/ascorbic acid increase free radical production. We wanted to verify whether melatonin has a protective effect against oxidative modifications and phosphatidylserine externalization in platelets induced by ox-LDL and Fe3+/ascorbic acid. For in vitro effects of melatonin on platelets, ADP-activated platelets were incubated with ox-LDL or Fe3+/ascorbic acid for 1 h at 37 degrees C with or without melatonin. Then platelet malondialdehyde, protein carbonyl and glutathione levels were measured. Platelet phosphatidylserine exposure was measured with annexin-V using flow cytometry. Malondialdehyde, protein carbonyl and phosphatidylserine levels of platelets treated with Fe3+/ascorbic acid significantly increased compared to the control group. Glutathione contents of Fe3+/ascorbic acid-treated platelets significantly decreased. Melatonin pre-treatment of Fe3+/ascorbic acid-treated platelets caused a mar ked reduction in malondialdehyde and phosphatidylserine levels and a marked increase in glutathione levels. Melatonin also caused non-significant reduction in protein carbonyl contents of Fe3+/ascorbic acid-treated platelets. Malondialdehyde, protein carbonyl and phosphatidylserine levels of platelets treated with ox-LDL also significantly increased compared to the control group. Platelet glutathione levels non-significantly decreased with ox-LDL. With addition of melatonin, malondialdehyde, protein carbonyl and phosphatidylserine levels of platelets treated with ox-LDL significantly decreased. These data suggest that melatonin may protect platelets from iron overload-induced and ox-LDL-induced oxidative modifications and also from the triggering signals of apoptosis activation, possibly due to its scavenger effect on toxic free radicals.
Keywords: Adult; Humans; Antioxidants; Melatonin; Glutathione; Lipid Peroxidation; Malondialdehyde; Oxidative Stress; Oxidation-Reduction; Lipoproteins, LDL; Blood Platelets; Ascorbic Acid; Ferric Compounds; Phosphatidylserines